A qualitative study of phenomenology of perspectives of student nurses: experience of death in clinical practice - ShiShuang Zhou; LiZhen Wei; Wei Hua; XioaChong He; Jia Chen (BMC, 2022)
Abstract Aim To describe the experiences of student nurses in confronting the death of their patients, and to understand how they cope with these events and to what extent there are unmet needs that can be addressed in their trainings. Methods Semi-structured interview method was used to collect data from Chinese nursing students and then Colaizzi's seven-step analysis method was applied to identify recurrent themes in their responses to patient deaths. We listened the tape repeatedly combined with observations of their non-verbal behaviors, then transcribed them with emotional resonance, and entered them into Nvivo. After that, we extracted repeated and significant statements from the transcriptions, coded, then clustered codes into sub-themes and themes which were identified by the comparation with transcriptions and re-confirmation with our participants. Results After confirmation from the interviewees, five themes emerged: emotional experience, challenge, growth, coping and support.